92.6k views
1 vote
Solve for n: c= 6n−5g /11t

User Evt
by
5.1k points

1 Answer

1 vote

Answer:
(11tc+5g)/(66t)=n

Explanation:

You have the equation
c=6n-(5g)/(11t).

Then, to solve for the variable
n from the equation you need:

Make the subtraction of the right side of the equation:

(As the denominators are 1 and
11t, the least common denominator is
11t)


c=((6n)(11t)-5g)/(11t)\\\\c=(66nt-5g)/(11t)

Multiply
11t to both sides:


(11t)c=((66nt-5g)/(11t))(11t)\\\\11tc=66nt-5g

Add
5g to both sides:


11tc+5g=66nt-5g+5g\\\\11tc+5g=66nt

And finally divide both sides by
66t:


(11tc+5g)/(66t)=(66nt)/(66t)\\\\(11tc+5g)/(66t)=n

User Mujjiga
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.